MELACAK MAKNA NUSYUZ DALAM AL-QUR’AN: ANALISIS SEMANTIK TOSHIHIKO IZUTSU - Husna, Rifqatul; Sholehah, Wardani (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
This study aims to understand the meaning of nusyuz in the Qur'an through Toshihiko Istuzu's semantic study. This is because there are different solutions when nusyuz is carried out by the husband (male) and wife (female), which seems to be in favor of the male. To find out the cause of these differences, it is necessary to trace the deep meaning of the meaning of nusyuz. This research uses qualitative methods from library data (library research) to produce answers and conclusions from these problems. Meanwhile, the data analysis used content analysis, which resulted in the conclusion that there was no difference in the meaning of nusyuz between husband and wife. The difference is only found in the solution taken when the nusyuz is carried out by the husband or wife, as is common and is explained in the text of the dhahir verse of the Qur'an (Q.S. Al-Nisa' (4): 34 and 128).